Still a mother : noncustodial mothers, gendered institutions, and social change - Krasas, Jackie, 1965- (Cornell University Press, 2021)
"Still a Mother is about the experiences of noncustodial mothers who have lost or ceded custody to an ex-partner. The author argues that these noncustodial experiences should be understood in the greater web of gendered social institutions such as employment, education, health care, and legal institutions that shape the meanings of contemporary experiences of motherhood in the United States."--